2018 IEEE 88th Vehicular Technology Conference (VTC-Fall) 2018
DOI: 10.1109/vtcfall.2018.8690644
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Shape of CAN Data for In-Vehicle Intrusion Detection

Abstract: Modern vehicles rely on scores of electronic control units (ECUs) broadcasting messages over a few controller area networks (CANs). Bereft of security features, in-vehicle CANs are exposed to cyber manipulation and multiple researches have proved viable, life-threatening cyber attacks. Complicating the issue, CAN messages lack a common mapping of functions to commands, so packets are observable but not easily decipherable. We present a transformational approach to CAN IDS that exploits the geometric properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…CAN IDS research into unsupervised learning methodologies for detecting malicious messages has begun modeling correlations inherent to the CAN data that are broken by attacks. Tyree et al [23] propose a manifold learning technique to identify relationships in CAN data that are broken during attacks that do not coordinate related signals. Their technique requires at least the ability to tokenize (partition) the up-to 64-bit CAN data fields into signal-sized messages but not fully translate the CAN data.…”
Section: Related Can Ids Workmentioning
confidence: 99%
“…CAN IDS research into unsupervised learning methodologies for detecting malicious messages has begun modeling correlations inherent to the CAN data that are broken by attacks. Tyree et al [23] propose a manifold learning technique to identify relationships in CAN data that are broken during attacks that do not coordinate related signals. Their technique requires at least the ability to tokenize (partition) the up-to 64-bit CAN data fields into signal-sized messages but not fully translate the CAN data.…”
Section: Related Can Ids Workmentioning
confidence: 99%
“…Attacks that seek to change vehicle states abruptly may manipulate the messages in an unexpected and discontinuous way. To test this hypothesis, we employed manifold learning techniques to learn a lower dimensional representation of CAN data and found that testing on emulated attacks shows a discontinuous jump in the lower dimensional representation providing a novel avenue for detection [Tyree, et al 2018]. The above method is a "black box" method (knowing nothing of the data's meaning, but identifying correlations mathematically), which detracts from interpretability.…”
Section: Michael F Wehner and Christina M Patricolamentioning
confidence: 99%
“…Some research opts for handlabeled drive states (i.e accelerate, reverse, key in, speedometer reading of 20mph, ect.) [7][8][9], while others used external data loggers [10].…”
Section: B Vehicle Information and Diagnosticsmentioning
confidence: 99%
“…Others implemented machine learning methods (Hidden Markov Models, Neural Nets, Manifold Learning, etc.) that implicitly learn relationships between raw binary data and vehicular states [7][8][9][10][16][17][18].…”
Section: E Impactmentioning
confidence: 99%